Moderating usability tests principles and practices for interacting - Dumas, Joseph S., 1943-; Loring, Beth A. (Amsterdam ; Boston : Morgan Kaufmann/Elsevier, 2008)
Many aspects of usability testing have been thoroughly studied and documented. This isn't true, however, of the details of interacting with the test participants who provide the critical usability data. This omission has meant that there have been no training materials and no principles from which new moderators can learn how to interact. Moderating Usability Tests is the place for new and experienced moderators to learn about the rules and practices for interacting that have never been described in one place before. Authors Dumas and Loring draw on their combined 40 years of usability testing experience to develop and present the most effective principles and practices - both practical and ethical --for moderating successful usability tests. To help usability professionals, students, and novices understand these principles, the authors provide videos from their lab that demonstrate good and poor interaction as well as commentary from a panel of testing experts on why certain techniques succeed or fail. The videos are accessible from the publisher's companion web site. . Presents the ten "golden rules" that maximize every session's value . Offers targeted advice on how to maintain objectivity . Discusses the ethical considerations that apply in all usability testing . Explains how to reduce the stress that participants often feel . Considers the special requirements of remote usability testing . Demonstrates good and bad moderating techniques with laboratory videos accessible from the publisher's companion web site.
Chapter 1: Introduction -- Introduction to the problem -- Goals of the book and videos -- A brief history of usability testing practice -- Part I: The rules of interaction -- Chapter 2: Your roles as administrator -- The gracious host -- The objective observer -- The tradeoffs between them -- Chapter 3: The Golden Rules -- -- Part 1: the Five Core Rules -- 1. The goals of the test and your relationship with developers determine why and when to interact -- 2. Respect the participants? rights -- 3. You have a responsibility to future users -- 4. The participants are the experts; you are in charge -- 5. Being?real? is being professional -- Chapter 4: The Golden Rules -- -- Part 2: Five Additional Rules -- 6. Let the participants speak -- 7. Your intuition can hurt and help you -- 8. Be unbiased -- 9. Don?t give away information inadvertently -- 10. Watch yourself to keep sharp -- Part II: Moderating the test session -- Chapter 5: First contact? Setting the tone -- Pre-test instructions -- Informed consent -- Chapter 6: Interacting During the Session -- Keeping the participant talking -- How much to interact -- Providing encouragement -- Dealing with stress -- Deciding when to give assistance -- How to move the participant along -- Chapter 7: Post-task activities -- What to do first -- Taking advantage of their knowledge -- Presenting ratings and questionnaires -- Making a good last impression -- Part III: Special topics -- Chapter 8: Interacting in a remote testing session -- Preparing for the session -- Getting the session started -- Interacting when you can?t see the participant -- Chapter 9: In the Room vs. Out of the Room -- Advantages and disadvantages of being in the room -- Advantages and disadvantages of being out of the room -- Chapter 10: Summing Up -- Where do we go from here? -- Advice for novice administrators.
Includes bibliographical references (p. 169-173) and index.
Keywords: Human-computer interaction; User interfaces (Computer systems) -- Testing; Electronic books